Impact of incorporating olive leaves during the industrial extraction of cv. Arbequina oils on the physicochemical--sensory quality and health claim fulfillment - Marx, Ítala M. G. (2022)
The effect of olive leaves addition (1%, w/w, cvs. Arbequina or Santulhana), during the industrial extraction of Arbequina oils, on their physicochemical, color, phenolic profile, and sensory characteristics, was studied. Leaves incorporation reduced the primary oxidation (peroxide value by 33% and K232 by 17%) and increased the oxidative stability (19%), with the impact being more pronounced for Arbequina leaves. For these latter oils, leaves incorporation increased the total phenolic content (293±9 mg GAE/kg), which became richer in secoiridoid derivatives (143.7±3.0 mg/kg). Also, only Arbequina oils extracted with their own leaves supported the health claim regarding the protection of blood lipids against oxidative stress (hydroxytyrosol and tyrosol derivatives content greater than 5 mg per 20 g of olive oil). On the other hand, the incorporation of leaves from cvs. Arbequina and Santulhana during extraction enhanced the bitterness (5559%) and decreased the pungency (2533%). Santulhana leaves promoted an increase of the green-fruitiness (5.3±0.5), while Arbequina leaves enhanced the oils sweetness (7.0±0.4). Moreover, a potentiometric laboratory-made electronic tongue was applied, as a taste sensor device, being capable of successfully discriminating Arbequina oils extracted without or with addition of leaves, allowing the identification of (un)deliberated leaves incorporation during oils extraction. Lastly, it was found that the quality and composition of Arbequina oils industrially extracted were leaf cultivar dependent, with the low level of phenolics of control oils promoted by the incorporation of Arbequina leaves.